Beyond influencers: exploring new promotional strategies of luxury fashion brands - Catarinella, Piermauro; Kram, Suhardi; Colombo, Omar; Husain, Muhammad Alhakeem (Faculty of Art and Design, 2025)
Over the past nine years, Chiara Ferragni has emerged as one of the most prominent influencers on the global stage, collaborating with numerous internationally renowned fashion brands to promote and endorse their products. However, since December 2023, her reputation has been significantly tarnished due to her involvement in a judicial investigation led by the Public Prosecutor’s Office of Milan. Ferragni faces charges of aggravated and continued fraud, with her trial set to commence on 23 September 2025. As a result, several high-profile fashion brands have severed their professional ties with her. This study employs a qualitative approach to examine both the ongoing legal proceedings against the 36-year-old influencer and the evolving marketing strategies that globally recognized fashion brands are adopting in response. Data was collected through a systematic review of diverse sources to provide a comprehensive analysis of the influencer industry and its dynamic relationships with brands and consumers. The findings suggest that the role of influencers like Chiara Ferragni, traditionally leveraged to drive sales of luxury products, has significantly diminished and emerging forms of advertising and marketing strategies are gaining prominence. Ferragni’s followers, representing a broader consumer base, appear to have developed a more critical and conscious perspective, showing reduced interest in influencer-led campaigns. The study concludes that the traditional influencer model, as it has been known in recent years, is likely to decline, paving the way for new paradigms in brand-consumer engagement.